Using Accreditation to Ensure the Quality and Safety of Medical Services - Szczurek, Teresa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The article presents the accreditation of hospitals as a recognised method of improving the safety and quality of the services provided. The attempt to endeavour the idea of accreditation in Poland was originated by the project, co-funded by the European Union, called “Supporting the process of accreditation health service institutions”, which was implemented from 2008 to 2014. The main purpose of the project was to improve the quality of healthcare by providing financial and substantive support for hospitals during the process of accreditation. The project’s participants were entities that carried out the provision based on contract with a public payer. 243 hospitals were evaluated, of which 78.6% (191) received positive recommendations from the Accreditation Council, while 21.4% (52) received negative recommendations. The visible results of systematisation in hospitals are that: hospital operations and staff conduct are standardised, a quality monitoring system is constructed by establishing measurable indicators, hospital activities with regards to respecting patients’ rights are streamlined and reorganised, human resource management is created, competence and responsibility are regulated, and the patient is made the priority in all activities. Based on these results, this hypothesis was established: Accreditation in the project „Supporting the process of accreditation of health care institutions” is an effective means of verifying and developing the quality and safety of medical services provided in hospitals. Consequently, accreditation should be considered an effective means of verifying and developing the quality and safety of medical services.